PENEGAKAN KEAMANAN LAUT INDONESIA TERKAIT ANCAMAN OPERASI MILITARY GREY ZONE OPERATION OLEH CINA DI LAUT CINA SELATAN BERDASARKAN UNCLOS 1982: ENFORCEMENT OF INDONESIA’S MARITIME SECURITY RELATED TO THE THREAT OF MILITARY GREY ZONE OPERATION BY CHINA IN THE SOUTH CHINA SEA BASED ON UNCLOS 1982 - Putra, Dzulfiqar Gondawa; Fitriliani, Yulia (Fakultas Hukum Universitas Trisakti, 2023)
The enforcement of maritime security within Indonesia is a manifestation of law enforcement and sovereignty over Indonesia's maritime zone. However, in practice there are still violations, including in the South China Sea adjacent to the North side of the North Natuna Sea. During 2022 to January 2023, China Coast Guard (CCG) ships owned by China conducted Military Gray Zone Operations in the North Natuna Sea which is an area of Indonesia's Exclusive Economic Zone (EEZ). The problem of this research is whether the operations carried out by the CCG ships in the North Natuna Sea violate Indonesia's EEZ and Continental Shelf based on the 1982 United Nations Convention on the Law of the Sea (UNCLOS 1982), and what efforts will be made by Indonesia against the threat of these operations. This research uses secondary data sources so that it is normative legal research, with analytical descriptive nature and deductive logic. The conclusion obtained is that the operations carried out by the CCG vessels are a violation of Indonesia's EEZ and continental shelf. This is because based on the 2016 Permanent Court of Arbitration (PCA) Decision, the nine dash line claim is not in accordance with UNCLOS 1982 and the EEZ has gained international recognition. Furthermore, the operation also violates the principle of navigation, which is that crossing the jurisdiction of the coastal state must be continuous without stopping to unless there is a valid reason according to law; the obligation to respect the rights and obligations, and comply with the laws and regulations of the coastal state (Article 58 paragraph (3)); and the obligation of good faith (Article 300) of UNCLOS 1982. Efforts made by Indonesia are through national (Indonesia Marine Security Agency) and international (diplomacy and legal channels).